2010
DOI: 10.3201/eid1603.091346
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Squirrel Monkeys with Nipah Virus

Abstract: We infected squirrel monkeys (Saimiri sciureus) with Nipah virus to determine the monkeys’ suitability for use as primate models in preclinical testing of preventive and therapeutic treatments. Infection of squirrel monkeys through intravenous injection was followed by high death rates associated with acute neurologic and respiratory illness and viral RNA and antigen production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 15 publications
1
40
0
1
Order By: Relevance
“…Detailed follow-up of virus dissemination within the host after transfer of virus-loaded leukocytes should allow further analysis of leukocytes in NiV spread. Accordingly, in experimentally infected squirrel monkeys, NiV is also detected only associated with PBMC and is not found in plasma (29). However, occasionally, virus was found in both blood cell and plasma compartments from African green monkeys and cats infected by NiV, although virus detection required RT-PCR with 50 cycles of amplification, suggesting that there was only a very small amount of free virus (18,30).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed follow-up of virus dissemination within the host after transfer of virus-loaded leukocytes should allow further analysis of leukocytes in NiV spread. Accordingly, in experimentally infected squirrel monkeys, NiV is also detected only associated with PBMC and is not found in plasma (29). However, occasionally, virus was found in both blood cell and plasma compartments from African green monkeys and cats infected by NiV, although virus detection required RT-PCR with 50 cycles of amplification, suggesting that there was only a very small amount of free virus (18,30).…”
Section: Discussionmentioning
confidence: 99%
“…Serological studies indicated that NiV occurred in dogs, cats, horses and goats in the outbreak areas of Malaysia but all were effectively dead-end hosts [84]. Apart from pigs, experimental infection has been produced in cats [64], golden hamsters [94] and squirrel monkeys (Saimiri sciureus) [62]. Experimental studies have shown that infected cats shed NiV through the nasopharynx and in urine during viremic phase and of 2 cats infected, one recovered from experimental NiV infection with a high neutralizing antibody titer within 21 days [64].…”
Section: The Host Rangementioning
confidence: 99%
“…Endogenous peroxidase was blocked with 0.6% H 2 O 2 in methanol for 20 min. The primary antibody was a mouse polyclonal, cross-reacting, anti-Hendra virus antibody used at a 1:2,000 dilution (38,61). Positive signals were revealed by linking secondary antimouse antibodies and diaminobenzidine as the substrate.…”
Section: Methodsmentioning
confidence: 99%